2016
DOI: 10.1007/s10815-016-0683-7
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate does not affect ovarian reserve or subsequent assisted reproductive technology outcomes

Abstract: Purpose The purpose of this research was to study whether methotrexate (MTX) as treatment for ectopic pregnancy (EP) impacts the future fertility of women undergoing assisted reproductive technology (ART) Methods In a systematic review and multi-center retrospective cohort from four academic and private fertility centers, 214 women underwent an ART cycle before and after receiving MTX as treatment for an EP. Measures of ovarian reserve and responsiveness and rates of clinical pregnancy (CP) and live birth (LB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
0
9
1
2
Order By: Relevance
“…In women who were treated with MTX for ectopic pregnancy, there were no differences in the FSH levels, antral follicle count, oocytes retrieved, or fertilization rate between pre-and post-MTX therapy. The cumulative dose of MTX in ectopic pregnancies was much lower than in this study [12][13]. Banas et al [14] reported that RA patients underwent menopause at a significantly younger age than healthy women but found no association with MTX treatment [14].…”
Section: Discussioncontrasting
confidence: 52%
“…In women who were treated with MTX for ectopic pregnancy, there were no differences in the FSH levels, antral follicle count, oocytes retrieved, or fertilization rate between pre-and post-MTX therapy. The cumulative dose of MTX in ectopic pregnancies was much lower than in this study [12][13]. Banas et al [14] reported that RA patients underwent menopause at a significantly younger age than healthy women but found no association with MTX treatment [14].…”
Section: Discussioncontrasting
confidence: 52%
“… 9 Hence, it is recommended that there should be a treatment‐free interval of 3 or more months between discontinuation of MTX regimen and conception. 9 , 10 On the other hand, some researchers suggested that MTX exerted no adverse effects on ovarian reserve and outcomes in assisted reproductive technology cycles in a large fertility cohort, 11 , 12 and female fertility was not negatively affected by MTX treatment based on the results of an anti‐Müllerian hormone (AMH) test. Nevertheless, although these statistical data suggest a low possibility of occurrence of detrimental effects on female reproductive mechanisms due to previous MTX medication, the conclusion based on these may not be applicable to every patient as prescription of medication in the clinical settings varies because of individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, MTX systemically administered, intramuscular injected or in situ injected, used alone or in combination with laparoscopy, has long been advocated as an alternative method resolving ectopic pregnancy [40][41][42][43]. Some research suggested MTX didn't exert significant adverse effect on fertility in both spontaneous fertile and infertile population [44,45]. In the case presented, we didn't choose MTX-based treatment to reduce trophoblast activity at the first place.…”
Section: Discussionmentioning
confidence: 94%